Special pattern of endochondral ossification in human laryngeal cartilages: X-ray and light-microscopic studies on thyroid cartilage - Claassen, Horst; Schicht, Martin; Sel, Saadettin; Paulsen, Friedrich (Clinical anatomy, 2014)
endochondral ossification; laryngeal cartilages; laryngeal ossification; thyroid cartilage